Non-square Multivariable System Control Case Study – Static Optimal Compensator Design and Application - Varga, Dominik; Honc, Daniel; Dušek, František (Springer Science and Business Media, 2021)
By multivariable decentralized control, changing one set-point in result acts as a disturbance to other control loops. This can be solved by using multivariable controller or compensator. In this paper, a novelty approach to control non-square eighth-order system with four inputs and three outputs is demonstrated using a static compensator that guarantees autonomy in the steady state (changing one input, affects one output) and also optimal solution for non-square overdetermined systems (systems with more manipulated variables than controlled variables). To evaluate the control quality of this method, the system is also controlled without static compensator for comparison.
Případová studie řízení vícerozměrných systémů - návrh a aplikace statického optimálního kompenzátoru
Keywords: control; MATLAB; non-square system; static compensator; řízení; MATLAB; nečtvercový systém; statický kompenzátor